The Environmental Suitability of Canaan District Well Water and Its Suitability for Human Use - Rashid, Nisreen Hadi (Journal of Tikrit University for Humanities, 2024)
The research deals with determining environmental suitability by studying the chemical and physical characteristics of (12) groundwater wells in the Canaan district, most of whose depths range between (17.9 - 24 metres). The study of the characteristics consisted of the main positive and negative ions to determine water quality, and through the results of laboratory analysis of samples taken for the wells. The samples selected for the research area, it showed the significant change in the chemical and physical properties of the water, and the extent of the possibility of groundwater contamination in the region due to leakage from surface sources of pollution, based on the geological, hydrological and hydrochemical conditions of the aquifer and water in the region. The research showed that there are areas of pollution with increased concentrations of most of the elements are below the permissible limits for human use in most locations in the region, and wells 7, 2, and 9 were identified as highly polluted, and wells 10 and 11 were suitable for human use. Several maps of the research area were drawn showing the distribution of groundwater wells in the region, as well as a statement of the chemical and physical elements, to take this into account when planning a new development project in the region so that these projects are not sources of groundwater pollution.